Cover Image, Volume 26, Issue 3. (5th February 2018) - Song, Yu Jin; Kang, Jeong‐Yoon; Baek, Gun Yeol; Bae, Jin A; Yang, So Hyun; Jeon, Chan‐Wook
Abstract : The cover image, by Yu Jin Song et al., is based on the Research Article Two‐step selenization using nozzle free Se shower for Cu(In, Ga)Se2 thin film solar cell, DOI:10.1002/pip.2976 .